Pengembangan Bahan Ajar Cerita Rakyat Keramat Riak Berbasis Audio Visual pada Pembelajaran Bahasa Indonesia untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 56 Kota Bengkulu - Indah Putri Utami; Abdul Muktadir; Irwan Koto (UNIB Press, 2024)
The aim of this research is to develop, describe the level of feasibility, determine user responses and determine the effectiveness of developing audio-visual-based Sacred Riak Folklore Teaching Materials in Indonesian Language Learning to Improve Class IV Student Learning Outcomes at SDN 56 Bengkulu City. The type of research used is research and development. The research model in developing teaching materials is the ADDIE model. The type of data used is quantitative and qualitative data using instruments in the form of interviews, needs analysis questionnaires, questions, expert validation sheets and user response questionnaires. Based on the research results, it can be concluded that the teaching materials that have been developed are suitable for use as teaching materials in class IV Indonesian language content. The expert validation results were 0.95 from material expert validation, 0.93 from design validation, and 0.94 from language expert validation. The user response was very good because the results of the analysis of the class IV teacher questionnaire showed a percentage of 90.8% with very good criteria. Meanwhile, the response from students obtained a percentage of 93.8% with very good criteria. The teaching materials developed are effective in improving the learning outcomes of class IV students at SD Negeri 56 Bengkulu City. This is based on the results of the average score for the experimental class which used audiovisual based teaching materials which obtained a score of 80 while the control class obtained a score of 70.56 so there was a significant difference between the control class and the experimental class.